In vitro fracture strength and modes of cast post and cores luted with self-adhesive resin-based cement - Marcos C Pomini; Marina M Machado; Giovanny de Paula Quadros; Lidia O B Pinheiro; Adriana P B Samra (Universidade Estadual de Campinas, 2019)
Aim: Cast post and core (CPC) is the main used post type; however, the biomechanical behavior of CPCs adhesively luted to the dentin is still unclear. Therefore, we aimed to evaluate the fracture resistance (FR) and fracture modes of teeth restored with CPCs luted with zinc-phosphate (ZP) or resin-based self-adhesive (SA) cements, as well as the influence of the coronal remnant. Methods: For that, 24 human premolars were divided into four groups according to the cement (ZP or SA) and coronal remnant (with or without 2mm). FR was tested in a universal machine and data analyzed by two-way ANOVA and Tukey HSD (α=.05). Fracture modes were classified according to the degree of dental destruction. Results: The results showed that there was no difference in FR (p=.352); however, teeth without ferrule presented more irreparable fractures, specially in the ZP group. Conclusion: All in all, self-adhesion of CPCs does not enhance fracture resistance, however it reduces the number of irreparable fractures, compared to ZP cement.